2018
DOI: 10.18805/ajdfr.dr-1340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maturity stages on shelf life of papaya (Carica papaya L.)

Abstract: An experiment using cv. Taiwan was 786 laid out in factorial completely randomized design with thirty treatments and three replications was, carried out at Laboratory of Horticulture Section, College of Agriculture, Dhule (M.S.) during 2017. The experiment comprised of three factors viz. two maturity stages (25% mature and 50% mature), dipping them in aqueous solutions of spermine (1.0 mM and 2.0 mM) and calcium lactate (1% and 2%) for 5 minutes and drying for 30 minutes at room temperature, three packaging ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…It causes a high concentration for the in vivo test. The results of the phytochemical screening of papaya leaves from Bandung were the same as those of Patil et al [ 17 ]. Therefore, the secondary metabolites for molecular docking and ADMET prediction were taken from the secondary metabolites that have been characterized.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It causes a high concentration for the in vivo test. The results of the phytochemical screening of papaya leaves from Bandung were the same as those of Patil et al [ 17 ]. Therefore, the secondary metabolites for molecular docking and ADMET prediction were taken from the secondary metabolites that have been characterized.…”
Section: Discussionsupporting
confidence: 59%
“…Papaya leaves showed no harmful effects on long-term administration [ 16 ]. Phytochemical screening showed that papaya leaves contain saponins, cardiac glycosides, anthraquinones, reducing sugars, flavonoids, alkaloids, and tannins [ 17 ]. Even though papaya has several critical medicinal properties, studies have yet to be performed to investigate its antidiarrheal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Many biotic factors include bacteria, fungi, viruses, virus-like organisms and nematodes, which infect the crops and retard the production yield (Kataria and Kumar, 2012) along with significant economic loss. Among these biotic factors, viruses create major constraints to agriculture production in India (Patil et al, 2018;Prabha and Modgil, 2018).…”
Section: Introductionmentioning
confidence: 99%